Energy mix diversification and financial development: Electricity in G20 countries - Riyana, Putri; Hartono, Djoni (Jurnal Ekonomi dan Bisnis, 2025)
Energy mix diversification is unique due to differences in resource potential, economic and environmental conditions in each country. The transition to renewable energy is one of the sustainable development agendas, as well as the G20's targets in addressing environmental issues and building energy security. However, in its implementation, a good financial system is needed to accommodate infrastructure development and construction. This study aims to analyze the role of financial development in influencing energy mix diversification, focusing on how progress in the financial sector can encourage a more diverse and sustainable energy transition. The fixed effect model and System-GMM estimator are employed in this study, using panel data samples from 19 members of G20 countries over a 22-year period. The estimation results show that financial development has a positive and significant effect on energy mix diversification. Therefore, strengthening financial systems both from the institutions and financial market side can play a crucial role in promoting a more balanced and inclusive energy transition. The results also show that the control variables energy efficiency, carbon emissions and FDI have a negative relationship to energy mix diversification, while economic growth has a positive relationship to energy mix diversification. These findings suggest that higher economic activity enhances a country’s capacity to expand energy diversification, whereas improvements in energy efficiency, higher carbon emissions, and profit-oriented foreign investment flows tend to limit efforts toward greater energy diversification.